Global white nationalism : From apartheid to Trump - Geary, Daniel; Sutton, Jennifer Ann; Schofield, Camilla, 1978- (Racism, resistance and social change., 2020)
This book offers the first transnational history of white nationalism in Britain, the US and the formerly British colonies of Rhodesia, South Africa and Australia from the post-World War II period to the present. It situates contemporary white nationalism in the 'Anglosphere' within the context of major global events since 1945. White nationalism, it argues, became more global in reaction to the forces of decolonisation, civil rights, mass migration and the rise of international institutions. In this period, assumptions of white supremacy that had been widely held by whites throughout the world were challenged and reformulated, as western elites professed a commitment to colour-blind ideals. The decline in legitimacy of overtly racist political expression produced international alliances among white supremacists and new claims of populist legitimation.